PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI SMA NEGERI KOTA SOLOK - Yuni Harnita; Suswati Hendriani; Elda Herlina (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2026)
This study aims to analyze the impact of school administration and school culture on teacher performance at Public Senior High Schools (SMA Negeri) in Solok City. The primary issue investigated is teacher performance, which is negatively influenced by the leadership attitudes of school principals and students. This research employs an ex post facto design with a quantitative approach. The research population consists of all teachers at Public Senior High Schools in Solok City, with a sample size of approximately 141 individuals. Data were collected using questionnaires that had been verified for validity and reliability. Data analysis techniques included multiple regression and simple regression. The results indicate that the principal's leadership has a significant impact on teacher performance (r = 0.869), the school budget also has a significant impact (r = 0.840), and both investigated variables have a significant combined impact on teacher performance (r = 0.869). This relationship is considered significant. Furthermore, the study's findings reveal that, with an R-squared value of 0.800, school culture and the principal's leadership have a significant impact on teacher performance. This implies that 80% of teacher performance can be explained by the variables of principal leadership and school culture, indicating the model's very high explanatory power. Ultimately, this study demonstrates that school administration and school culture are crucial factors influencing teacher performance. The implications of this study highlight the need for school principals to strengthen their leadership skills and foster a professional, cooperative, and team-oriented learning environment.